Implementasi Kebijakan Kawasan Tanpa Rokok di Rumah Sakit Umum Daerah (RSUD) UNDATA-Palu - budiwan, sadri (An Idea Nursing Journal, 2022)
RSUD UNDATA Palu is a health service facility that should have 100% to implement the area without cigarettes but until now there are still visitors who do the activity of smoking in the corridor even in the hospital room. Based on Palu City Regulation No. 3 of 2015 on non-smoking areas that are not allowed to engage in smoking activities in areas that have been designated as non-smoking areas, including in health care facilities. The purpose of this study is to know the concept of communication, resources, disposition and bureaucratic structure in the Implementation of Regional Regulation of Palu City No. 3 of 2015 about non-smoking areas in RSUD UNDATA Palu. The research method used is qualitative research with case study approach. The result is that the concept of communication is good enough. KTR Task Force in RSUD UNDATA uses printed and electronic media. In the variable resources obtained results that are not good enough. The KTR taskforce at RSUD UNDATA is still less than the number that there are only 15 people who previously amounted to 30 people. In the disposition variable obtained in this study is good enough. The appointment of the KTR taskforce at UNDATA Hospital was directly elected by the hospital director, but the supervisory officers still lacked incentives. In the variable of bureaucracy structure got good result. The most authorized in implementing implementation of KTR policy implementation in RSUD UNDATA Palu is coordinator of task force. Suggestions in this research KTR Task Force in RSUD UNDATA should be added plus and the RSUD UNDATA to make smooking area.